2015
DOI: 10.21831/socia.v10i1.5343
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pendekatan Values Clarivication Technique (Vct) dalam Pembelajaran IPS di Sekolah Dasar

Abstract: Penelitian bertujuan untuk mengimplementasikan pendekatan Values Clarification Technique (VCT) dalam pembelajaran IPS di SD Sekarsuli, Banguntapan, Bantul, Yogyakarta. Menggunakan metode kualitatif deskriptif, subjek penelitian siswa kelas V. Pengumpulan data melalui observasi, wawancara, catatan lapangan dan analisis dokumen. Analisis data secara kualitatif dengan teknik yang dikembangkan Miles dan Huberman. Hasil penelitian menunjukkan bahwa dengan penerapan teknik klarifikasi nilai, proses pembelajaran IPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Pembelajaran yang menggunakan model VCT mengarahkan siswa untuk terlibat langsung dalam pembelajaran, menuntut siswa untuk aktif dan berinteraksi dengan siswa yang lain. VCT membantu siswa dalam mengklarifikasi nilai, memecahkan masalah, berdialog, berdiskusi, dan mempresentasikan ide (A. T. Wijayanti, 2015); (Kirschenbaum, 2013). Materi Pendidikan Kewarganegaraan dan Ilmu Pendidikan Sosial merupakan materi yang di dalamnya membutuhkan diskusi, komunikasi dan berinteraksi.…”
Section: Meta-analisisunclassified
“…Pembelajaran yang menggunakan model VCT mengarahkan siswa untuk terlibat langsung dalam pembelajaran, menuntut siswa untuk aktif dan berinteraksi dengan siswa yang lain. VCT membantu siswa dalam mengklarifikasi nilai, memecahkan masalah, berdialog, berdiskusi, dan mempresentasikan ide (A. T. Wijayanti, 2015); (Kirschenbaum, 2013). Materi Pendidikan Kewarganegaraan dan Ilmu Pendidikan Sosial merupakan materi yang di dalamnya membutuhkan diskusi, komunikasi dan berinteraksi.…”
Section: Meta-analisisunclassified
“…The development in the global era always has a big tendency for rapid changes in various aspects of life such as science and technology, transportation, communication, lifestyle, as well as values and traditions (Karta et al, 2022;Rindawan et al, 2020). Changes that occur can have a positive impact that supports progress and improves the quality of life, but can also have a negative impact on character and morality (Jaya, 2019;Wijayanti, 2015). This condition requires to realize the importance of strengthening character education as a foundation for quality human resource development, adapting in a dynamic world, Tissa Alifiyarti / How the Teacher's Efforts to Instilling Responsibility Character in Learning from Home Era?…”
Section: Introductionmentioning
confidence: 99%
“…This is a demand of the purpose of Indonesia's national standard of education, which is to educate the life of the nation. These demands make motivation and positive benchmarks in carrying out a good and competent learning process in the classroom (Khairunisa, 2017;Wijayanti, 2015). Therefore, the quality of learning will depend heavily on human resources such as teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research from Byford et al (2009) concluded that the use of value clarification discussion techniques for social science learning proved to be a valuable method to increase student awareness in society and help students to develop and facilitate understanding of specific issues, improve critical thinking skills, and improve interpersonal skills. Furthermore, Wijayanti (2015) conducted research that showed that learning by applying the VCT learning model can bring about positive behavior of learners such as aspects of religious values and devout worship, tolerance towards others, discipline, concern for friends, deliberation, and responsibility in completing tasks on time both individuals and groups. There is also research from Khairunisa (2017) that proves that through the VCT learning model, it explains that students become more understanding about social problems and social values and make social science learning more meaningful and instill the values of social care logically.…”
Section: Introductionmentioning
confidence: 99%